Unraveling the ambiguity of the commonality element in Indonesian class action litigation - Susilo, Erwin; Nahdhah, Nahdhah; Negara , Dharma Setiawan (International Journal of Law, Environment, and Natural Resources, 2026)
The meaning of commonality in Class Action (CA) lawsuits in Indonesia, which remains abstractly formulated, leaves room for judges to interpret it differently, potentially leading to "disparities in rulings and legal uncertainty." This research aims to compare the regulation of CA in Indonesia and the United States, specifically regarding the concept of commonality, and to formulate a more concrete and applicable concept for the Indonesian legal system. The normative legal research used in this study employs a legislative and comparative law approach. Based on the study, this research found that in the United States, commonality has developed more clearly through jurisprudence by emphasizing a single core issue (common contention) and the dominance of a shared issue (predominance), unlike Indonesia, which still lacks a definite standard. From this condition, this research takes a firm position that commonality should not be merely interpreted as a general similarity, but rather as a unity of substantive issues that can be proven and resolved collectively in a single decision. On this basis, it is necessary to formulate a norm that is "concrete, measurable, and operational" so that the CA mechanism can truly provide legal certainty.